Kewajiban dan Tujuan Da’wah dalam Perspektif Al-Qur’an dan Hadits - Maemunah, Yayah; Sitika, Ahmad Junaedi (Lembaga Yasin AlSys, 2023)
Da'wah is duty for all adult muslim . Da'wah can be carried out by all Muslims according to their knowledge, according to their capabilities, according to their capacities wherever they are. Da'wah can be carried out with a variety of strategies, methods and media. Da'wah can involve various groups, both individuals, groups or institutions. Da'wah media can be through print media or electronic (digital) media. Print media such as newspapers, magazines, bulletins, tabloids, and so on. Meanwhile, electronic (digital) media such as YouTube, TikTok, Instagram, websites, and so on. Da'wah can be done anywhere as needed, such as at the mosque, at the prayer room, at the Majlis Ta'lim, at Madrasahs, at institutions government or private, and so on. The purpose of da'wah is to invite others to the straight path, the path that is approved by Allah SWT. If da'wah to non-Muslims means inviting them to convert to Islam, whereas if preaching to Muslims means to increase their faith and piety to Allah SWT.In Alqur’an and Hadits many clauses and argumentations about obligation and purpose of da’wah . Because as we know, the Qur'an and Hadits are a source of guidance for Muslims in doing deeds, both mahdhoh and ghoiromahdhoh. As will be discussed in the following article, regarding the obligations and objectives of da'wah from the perspective of the Qur'an and Hadits.